Oral dysbiosis in children with renal failure: a systematic review - Juan Antonio Ruiz-Roca; María Pilar Pecci-Lloret; Antonio Romano; Francesco Carinci; Dorina Lauritano; Nuria Pérez-Guzmán; Alberta Lucchese (Frontiers in Dental Medicine, 2026)
Introduction The oral microbiome plays an important role in maintaining host homeostasis and may interact with systemic diseases through the oral–systemic axis. Chronic kidney disease (CKD) in childhood is associated with chronic inflammation, metabolic alterations, and immune dysfunction, which may influence microbial ecosystems. While intestinal dysbiosis has been widely studied in paediatric CKD, alterations in the oral microbiome remain less well understood. The aim of this study was to qualitatively synthesize evidence on oral microbiome alterations in children and adolescents with CKD compared with systemically healthy controls. Methods A systematic review was conducted according to PRISMA 2020 and registered in PROSPERO (CRD420261334000). PubMed, Scopus, Web of Science, Cochrane, and SciELO were searched (February 24, 2026). Eligible studies included participants aged 0–18 years with CKD (any stage), dialysis, or kidney transplantation and a healthy control group. Risk of bias was assessed using JBI and ROBINS-I v2 tools. Results From 109 records, 7 studies were included. Most used saliva, tongue/oral swabs, or dental plaque, and 16S rRNA sequencing was the most frequent method. Five studies reported oral dysbiosis in CKD, including severe dysbiosis grades in adolescents with end-stage disease, while two studies reported no significant differences versus controls. Conclusion Findings on individual taxa were inconsistent across studies, likely due to heterogeneity in renal phenotype, oral niche sampled, and analytical methods. Evidence suggests that salivary biochemical alterations (notably urea and pH) and inflammatory burden may influence microbial composition, whereas the tongue microbiome may show relative ecological stability in some paediatric cohorts. Children and adolescents with CKD may present oral microbiome alterations, but current evidence is limited by methodological heterogeneity and moderate-to-high risk of bias. Standardized sampling and longitudinal multicentre studies are needed to determine robust microbial signatures and their value as non-invasive biomarkers in paediatric nephrology. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420261334000 .